Beauty and the Eye of the Beholder: Gender and Attractiveness Affect Judgments in Teacher Sex Offense Cases. (June 2017) - Mackelprang, Emily; Becker, Judith V.
The present study investigated the effects of gender and attractiveness on judgments of bail requirements, incarceration, and sex offender registration lengths, and attitudes toward offenders and victims in a teacher–student sexual perpetration scenario. Researchers presented 432 undergraduate students at a large southwestern university with one of four vignettes detailing a sexual relationship between a 35-year-old teacher and a 14-year-old student. Vignettes varied by both attractiveness and gender of the offender (using heterosexual offender–victim dyads). Results indicate that both gender and attractiveness affect judgments of sex offenders; specifically, female sexual offenders were viewed more leniently and judged less punitively than male sexual offenders. Although attractive female sexual offenders were given particularly lenient treatment, attractiveness did not affect judgments toward male sex offenders. In addition, although male and female participants tended to rate male offenders similarly, male participants were more lenient toward female offenders than were female participants. Finally, post hoc analyses revealed that, for many variables, unattractive female sexual offenders may not be viewed differently from male sexual offenders. These results have serious implications for the legal system, sex offender management, and societal views regarding male and female sexual offenders and their victims.